Avaliação dos efeitos de 5-hidroxitriptofano e m-hidroxibenzilhidrazine associados a Lactobacillus spp. na morfometria intestinal e imunomarcação de serotonina em frangos de corte desafiados com Salmonella Enteridis - Donato, Taís C. [UNESP]; Baptista, Ana Angelita S. [UNESP]; Smaniotto, Bruna D. [UNESP]; Garcia, Keila C.O.D. [UNESP]; Okamoto, Adriano S. [UNESP]; Sequeira, Julio L. [UNESP]; Andreatti Filho, Raphael L. [UNESP] (FapUNIFESP (SciELO), 2015)
Enterochromaffin cells are components of the intestinal mucosa to release serotonin lumen, promoting cell growth and secretory activity of various tissues, including intestinal villi. This study evaluated the influence of 5-hydroxytryptophan (5HTP) and m-hidroxibenzilhidrazine (NSD1015) associated with Lactobacillus spp. on body weight and development of intestinal villi in the proximal duodenum of broilers challenged with Salmonella Enteritidis. It was found that the presence of Lactobacillus spp. and Salmonella Enteritidis influenced immunostaining of serotonin in the duodenum. The study was divided into two experiments with and without challenge by S. Enteritidis. In Experiment 1, birds without challenge, body weights did not differ significantly (p > 0.05), and in Experiment 2, the treatments with precursor and precursor associated with Lactobacillus spp. determined higher body weight of the birds. In both experiments the birds treated with 5HTP showed increased density and villus height in the duodenum, suggesting the presence of 5HTP as a trophic agent. The use of Lactobacillus spp. also determined greater duodenal villus height. The immunostaining of serotonin, birds treated with Lactobacillus spp. in Experiment 1, and the birds treated with Lactobacillus spp. and challenged with S. Enteritidis in Eperiment 2 showed higher values, suggesting that the presence of these bacteria promotes greater release of serotonin into the duodenum. The exact mechanism of how this process occurs needs to be further elucidated.
Assessment of the effects of 5-hydroxytryptophan and m-hydroxybenzyl hydrazine associated with Lactobacillus spp. in intestinal morphology and immunostaining of serotonin in broilers challenged with Salmonella Enteritidis
Keywords: Broilers; Intestinal morphology; Lactobacillus spp.; Salmonella Enteritidis; Serotonin